TANGGAPAN TERHADAP RANCANGAN UNDANG-UNDANG TENTANG HUKUM MATERIL PERADILAN AGAMA BIDANG PERKAWINAN - Aah Tsamrotul Fuadah (Institut Agama Islam Sahid Bogor, 2020)
Sirri marriage is again a hot issue in Indonesia, this surfaced when the proposed Draft Law (RUU) on the Material Law of the Religious Courts on Marriage or popularly known as the Siri Marriage Bill, which threatened the perpetrators of unregistered marriage with criminal sanctions, namely the various punishments, ranging from 6 months to three years, and fines from Rp. 6 million to Rp. 12 million. This bill invites pros and cons, those who agree think that this is a progress because according to them, sirri marriages often only harm women and have a negative impact on the offspring of sirri marriages. Meanwhile, the opposing parties argue that this bill will actually direct people to legalize adultery.In classical fiqh studies, sirri marriage is a marriage that is carried out without a guardian or witness, while the current definition of sirri marriage is more meaningful marriage which is carried out only according to their respective religions without being recorded in front of the Office of Religious Affairs. If sirri marriage is interpreted in the first sense, the scholars agree that marriage is invalid without a guardian and witness. As for sirri marriages that are carried out in Islam but are not recorded by KUA officials, most scholars consider them valid.This is where the problem arises regarding unregistered marriages in Indonesia, if this bill has been passed, the perpetrators of unregistered marriages will be subject to fines or imprisonment. Carrying out a marriage legally according to Islamic law as regulated in Article 2 paragraph (1) of Law Number 1 of 1974 is the embodiment of obedience to Allah and His Messenger in the matter of marriage. Meanwhile, implementing Article 2 paragraph (2) concerning marriage registration is a form of obedience to the leader. However, even though the rules of Allah and His Messenger as well as humans are very good, there will still be those who violate these rules. The proof is that there are still many Muslims who marry without being recorded, even though it is for the benefit of all parties, while that benefit is the goal of syara' (maqashid al-syari'ah).So from here, it is appropriate for those who carry out unregistered marriages because of financial problems, they must be assisted in carrying out their itsbat marriage to the Religious Courts by litigating for free (free). Meanwhile, those who perform unregistered marriages for other reasons, are recommended to perform itsbat nikah. If they don't want to, then they should be given sanctions both administratively and with criminal sanctions that can be a deterrent.